Carbon nanotubes and their use for asphalt binder modification: a review. Issue 2 (19th February 2020) - ul Haq, Muhammad Faizan; Ahmad, Naveed; Jamal, Muhammad; Anwar, Waqas; Khitab, Anwar; Hussan, Sabahat
Abstract : In recent years, various nanomaterials have been used in many scientific and engineering fields. Owing to their small size and large surface area, nanomodifiers result in improved substrate characteristics in comparison with their macro- and micro-sized counterparts. Nanomaterials possess incredible features that make them suitable as additives in asphalt mixtures. This study describes the importance of nanomaterials with emphasis on the use of carbon (C) nanotubes (CNTs) as asphalt binder modifier. Different methods for synthesis of CNTs, such as arc discharge, laser ablation and chemical vapor deposition, are explained, and different types of techniques used for CNT dispersion in bitumen are elaborated. The results of conventional testing techniques such as penetration grade, softening point, ductility and viscosity tests to characterize the mechanical performance of CNT-modified asphalt binders are also summarized in this work. Effects of CNT modifications on the rheological properties of an asphalt binder are also described. A systematic review of experimental studies on asphalt binder modification using CNTs was carried out. Addition of CNTs improves the stiffness of an asphalt binder, thereby increasing its resistance against rutting. Different parameters/variables such as binder type, mixing technique, mixer type, CNT properties and mixing time play key roles in modification of bitumen with CNTs by significantly affecting the performance of the resulting asphalt binder.